Perbandingan Metode Alih Ragam Hujan Menjadi Debit dengan FJ. Mock dan NRECA di DAS Welang Kabupaten Pasuruan - Anindya, Devita Putri; Suhartanto, Ery; Fidari, Jadfan Sidqi (Fakultas Teknik, Universitas Brawijaya, 2022)
The transformation of rain to discharge is a modeling process that converts rain data into discharge data. Discharge data in a watershed (DAS) is needed to determine the availability of water discharge in a river that will be used to meet the needs of living things around it. However, the availability of river flow data is often incomplete. Therefore, a change in the variety of rain to discharge is needed. This study aims to determine the results of the calculation of the conversion of rainfall into discharge at the Welang watershed location, Pasuruan Regency. The method used is the FJ. Mock and NRECA methods. The calculation results from these two methods will be compared with the AWLR data in the Welang watershed. From the results of the analysis, it was found that the most suitable method for calculating the transfer of rainfall into discharge in the Welang watershed is the FJ. Mock method with an NSE value of 0.629, a PBIAS value of 0.437, and a correlation coefficient (R) of 0.793. The use of the surrounding land influences the discharge condition in a watershed. The relationship between changes in land use and the condition of the annual average discharge of the Welang watershed shows that the discharge value tends to decrease in terms of comparisons in 2006, 2010, 2015, and 2020.Â Alih ragam hujan menjadi debit merupakan proses permodelan yang mengubah data hujan menjadi data debit. Data debit pada suatu daerah aliran sungai (DAS) diperlukan untuk mengetahui ketersediaan debit air pada suatu sungai yang akan dipergunakan untuk memenuhi kebutuhan makhluk hidup disekitarnya. Tapi pada kenyataannya ketersediaan data debit aliran sungai sering kali tidak lengkap, Maka dari itu dibutuhkan suatu alih ragam hujan menjadi debit. Pada studi ini bertujuan untuk mengetahui hasil perhitungan alih ragam hujan menjadi debit pada lokasi DAS Welang, Kabupaten Pasuruan. Metode yang digunakan adalah metode FJ. Mock dan NRECA. Hasil perhitungan dari kedua metode tersebut nantinya dibandingkan dengan data AWLR pada DAS Welang. Dari hasil analisis didapatkan bahwa metode yang paling sesuai untuk perhitungan alih ragam hujan menjadi debit pada DAS Welang adalah metode FJ. Mock dengan nilai NSE sebesar 0,629, nilai PBIAS sebesar 0,437 dan nilai koefisien korelasi (R) sebesar 0,793. Kondisi debit pada suatu DAS dipengaruhi oleh penggunaan lahan disekitarnya. Hubungan antara perubahan tata guna lahan dengan kondisi debit rerata tahunan DAS Welang menunjukkan nilai debit yang cenderung menurun, ditinjau dari perbandingan tahun 2006, 2010, 2015 dan 2020.